PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN TEKNOLOGI DI BEI DENGAN CSR SEBAGAI VARIABEL MODERASI - Kadek Dandy Arta Dhana; I Gede Agus Pertama Yudantara (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the effect of financial performance on stock prices, moderated by Corporate Social Responsibility. Financial performance is measured using the Current Ratio, Return on Equity, and Debt to Assets Ratio. This research is motivated by the phenomenon of stock price movements that are not aligned with financial performance and the role of CSR in shaping investor perceptions. A quantitative approach was applied using secondary data from annual reports of technology companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample was selected using purposive sampling, resulting in 17 companies as research subjects. Data were analyzed using multiple linear regression and moderating regression analysis. The research findings are as follows (1) CR has a negative effect on stock prices, (2) ROE has a positive effect on stock prices, (3) DAR has a positive effect on stock prices, (4) CSR weakens the effect of the CR, (5) CSR weakens the effect of the ROE on stock prices, and (6) CSR strengthens the effect of the DAR on stock prices.